2022
DOI: 10.4081/jbr.2022.10725
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon mapping in spider monkey genomes of the family Atelidae (Platyrrhini, Primates) shows a high level of LINE-1 amplification

Abstract: To investigate the distribution of LINE-1 repeat sequences, a LINE-1 probe was Fluorescence In Situ Hybridized (FISH) on the chromosomes of Ateles geoffroyi and Ateles fusciceps (Atelidae); a LINE-1 probe was also mapped on Cebuella pygmaea (Cebidae) and used as an outgroup for phylogenetic comparison. Ateles spider monkeys have a highly rearranged genome and are an ideal model for testing whether LINE-1 is involved in genome evolution. The LINE-1 probe has been mapped in the two Atelidae species for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…The post-FISH C banding pattern obtained was compared with previously published C banding of phylogenetically close species such as S. apella (Dumas et al 2022). Chromosomes pairs with evident C bands were: 8, 11, 18-20; other C bands were at the centromeres of acrocentric chromosomes (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The post-FISH C banding pattern obtained was compared with previously published C banding of phylogenetically close species such as S. apella (Dumas et al 2022). Chromosomes pairs with evident C bands were: 8, 11, 18-20; other C bands were at the centromeres of acrocentric chromosomes (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Metaphases were obtained from lymphoblast cell cultures in RPMI culture medium, following standardized protocols. Cell harvesting was performed after 3 h incubation with colcemid 10 μL (10 μg/mL Gibco), followed by hypotonic treatments of 0.075 M KCl for 20 min at 37 °C, following standard protocols (Dumas et al 2022). Metaphases of the analyzed species were stained pre-and post-FISH using chromomycin A3 (CMA3) and 4',6-diamidino-2-phenylindole (DAPI) staining, according to a recent protocol (Lemskaya et al 2018), with some adjustments.…”
Section: Methodsmentioning
confidence: 99%
“…Fibroblasts from skin biopsies after cell dissociation with collagenase IV (0.0186 g in 4 mL) for 1 h at 37 °C were maintained in DMEM medium (Dulbecco’s Modified Eagle medium, Sigma-Aldrich, Saint Louis, MO, USA), supplemented with antibiotics (1%) and fetal bovine serum (15%) at 37 °C for 72 h. Metaphases were obtained from fibroblast cell cultures after 1h of colcemid treatment (0.05 g/mL), followed by incubation with 0.075 M KCl (10 min at 37 °C) and Carnoy’s fixative (3 methanol:1 acetic acid) [ 41 ]. GTG-banding was produced by trypsin digestion following a previously-described protocol [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was performed in order to clarify the phylogenetic and systematic inferences regarding the tribe. Moreover, telomeric sequence probes were mapped by FISH in C. petaurista because recent works have suggested that interstitial telomeric sequences (ITSs) may be linked to the high rate of chromosome evolution in primates [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%